Modelo para determinar la densidad y el factor de expansión de mezclas multicomponentes de hidrocarburos en fase líquida - Barrera Vela, Richar Nixon (2025)
The purpose of the research was: to develop the model that allows determining the density and expansion factor of multicomponent mixtures of hydrocarbons in the liquid phase, for which the Peng-Robinson, Lee-Kesler and Raoult equations were combined. Three mixtures were used, which are indicated with their respective molar composition: Camisea natural gas (GNC) (88.54 % methane, 10.32 % ethane, 0.02 % propane, 0.54 % nitrogen and 0.58 % carbon dioxide); liquefied natural gas (GNL) (85 % methane, 10 % ethane and 5 % propane), and liquefied petroleum gas (GLP) (60 % propane and 40 % n butane). The results when applying said model indicate that GNC has a density and expansion factor of 457.856 kg/m3 and 621.458, with the temperature being 111.15 K and the pressure being 1.14357 atm. In the same way, the density and expansion factor for GNL were: 471.496 kg/m3 and 601.763, being at 111.15 K and 1.00206 atm. Finally, when applying the model for LPG, the density and expansion factor resulted: 539.304 kg/m3 and 260.996, being at 280.15 K and 5.00105 atm.These results were compared with those obtained using the Aspen HYSYS V14.0 simulator and with other sources, from which it was verified that the developed model determines with great accuracy the density and expansion factor of multicomponent mixtures of hydrocarbons in the liquid phase. In conclusion, the general objective was met and the general hypothesis was tested.